1973
DOI: 10.2337/diab.22.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Action of Growth Hormone and Thyroxine on Aortas of Hypophysectomized Dogs

Abstract: Young dogs were surgically hypophysectomized and maintained for eleven weeks postoperatively with age-matched normal controls. For three weeks prior to sacrifice, four hypophysectomized dogs were given daily injections of bovine growth hormone (GH, 0.2 mg./kg.) and another four were given daily injections of thyroxine (T 4 , 5 /tg-/ kg.). Aortas were removed, cleaned of adventitia and divided into three segments: arch, thoracic and abdominal. Each portion was analyzed for collagen, elastin, deoxyribonucleic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…We have reported previously that various segments of the arterial system show differences in response to disturbances in endocrine homeostasis such as diabetes [11,17], hypophysectomy and replacement therapy with pharmacological doses of a variety of hormones [10,11,16,17]. This differential hormone sensitivity was apparent also in the present series of experiments in both diabetic and hypophysectomized dogs treated with insulin.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We have reported previously that various segments of the arterial system show differences in response to disturbances in endocrine homeostasis such as diabetes [11,17], hypophysectomy and replacement therapy with pharmacological doses of a variety of hormones [10,11,16,17]. This differential hormone sensitivity was apparent also in the present series of experiments in both diabetic and hypophysectomized dogs treated with insulin.…”
Section: Discussionsupporting
confidence: 63%
“…Although all four GAG fractions were measured in eight arterial segments, only the data significantly different (p < 0.01) from hypophysectomized controls are presented. No comparison between normal and hypophysectomized dogs is given, since it is known that hypophysectomy itself significantly lowers the arterial GAG content [10,11,15,16], and this is not a point at issue. The effect of insulin on the GAG distribution in hypophysectomized dogs was not strictly comparable to that seen in diabetic dogs.…”
Section: Hypophysectomized Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the experimental work has been done on aortic tissue of small animals and it was tacitly assumed that the results were rep resentative of metabolic properties of the ar terial system in general (12). On the other hand, we have reported that the glycosamino glycan (GAG) content of such diverse vessels as aorta, coronary and renal arteries is by no means uniformly altered in dogs following hypophysectomy and hormonal replacement therapy (2,3,(13)(14)(15). Indeed, marked dif ferences in response were observed even amongst the three aortic segments, the aortic arch being less sensitive to alterations in hor mone homeostasis than were the thoracic and abdominal segments (2).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown in our laboratory that (a) removal of the hypophysis in the dog reduced the glycosaminoglycan (GAG) content of both aorta and coronary arteries, and (b) replacement therapy with soma totropin (STH), thyroxine, estrogen, progesterone or testosterone was ca pable of raising the GAG content in various aortic segments, but had no significant effect on coronary arteries [2,17,18]. This sort of difference in sensitivity prompted us to study the effect of hormones also on other arteries of the canine vascular tree -in this case the renal arteries.…”
Section: Introductionmentioning
confidence: 99%